Bogota Bag in Abdominal Compartment Syndrome at Kathmandu Model Hospital - Joshi, Bijendra Dhoj; Koirala, Udaya; Upadhyaya, Amit Mani; Joshi, Arbin; Dhital, Saroj (Journal of Nepal Health Research Council, 2017)
Background: The gold standard of quick and definitive treatment of Abdominal compartment syndrome (ACS) is surgical decompression by opening the abdomen and leaving it open until intra-abdominal pressure decreases. Temporary abdominal closure techniques are used to postpone definite closure until predisposing factors causing pathologic elevation of intra-abdominal pressure are resolved.This study aim to analyze feasibility of Bogota Bag placement as a way of temporary abdominal closure.Methods: Cases admitted in the period of eight years that were diagnosed to have or at risk to develop ACS and managed with ‘Bogota Bag’, irrespective of primary diagnosis were reviewed retrospectively. Cause of ACS, reasons to place Bogota bag, its complications and final outcome in terms of mortality related or not related with Bogota Bag placement were assessed.Results: Total of ten patients had placement of Bogota Bag in the period of eight years. Laparotomy for bowel perforation with peritonitis was the most common primary condition contributing to ACS. Bogota bag was placed in two cases after emergency decompression as a therapeutic measure whereas others were done as prophylactic measure. There were two mortalities (20%) which were not directly related to abdominal compartment syndrome. Conclusions: Abdomen closure with Bogota Bag for patients with ACS or likely to develop ACS is a feasible technique with minimal procedure related morbidities.